Strengthening Disaster Awareness Through The Village Command Center System (Sycordes) And Empowering Village Tourism Actors In Selok Awar Awar Kec. Pasirian Kab. Lumajang - Ridho'i, Mohammad; Fauzi, Moch; Likasari, Gati Ayu; Harwiki, Wiwiek; Augustinah, Fedianty; Hartati, Fadjar Kurnia (TRANSFORMASI : JURNAL PENGABDIAN PADA MASYARAKAT, 2024)
Selok Awar-Awar Village is located in the southern part of Pasirian Sub-district, Lumajang Regency, East Java, and is directly adjacent to the Indian Ocean to the south. This location provides great potential for the development of beach tourism, especially Watu Pecak Beach which offers natural beauty and culinary tourism, but the lack of security and safety facilities for tourists and MSME actors is a big problem for this tourism, considering that this tourism has great potential for natural disasters such as tsunamis and floods. The purpose of this service is to increase disaster awareness capacity and also improve the security, safety and comfort of tourists and tourism actors through the Village Command Center System (SYCORDES). The methods used are socialization, education and training on disaster mitigation, proposed zoning of tourist attractions, application of hygiene, production and marketing of products. To measure the success rate of the activity implementation, pre-test and post-test were conducted. Socialization conducted with activity partners and target partners resulted in collaborative support by BPBD and BMKG Lumajang District for the implementation of the kosabangsa activities. The results of education and training show that more than 44% of target partners have understood and practiced disaster mitigation with sycordes technology, zoning views of tourist attractions, application of hygiene, production and marketing. The activities carried out by the kosabangsa service team have succeeded in increasing the level of knowledge and skills of activity partners in increasing disaster awareness capacity and also increasing the security, safety and comfort of tourists and tourism actors.